SISTEM INFORMASI PENDAFTARAN PERNIKAHAN PADA KANTOR CATATAN SIPIL DI KOTA BINJAI - Fina Nilam Sari; Suci Ramadani (STMIK KAPUTAMA, 2020)
The Population and Civil Registry Office of Binjai City is a government agency which is engaged in providing services to the community. In running a marriage registration service, the binjai city Population and Civil Registry service serves Marriage registration for about 10 days because the system used is still not computerized or still manual with a collection of document files. So it takes a very long time in the process. Therefore to achieve less effective and efficient time in registration. Then the making of an online Marriage Registration Information system will be made which will greatly facilitate the marriage registrar's administrators. Using a website base with the programming language used is PHP. So that it will be easy to use many kinds of devices, both laptops, computers, mobile phones, and smartphones. The information system is made according to procedures in the Population and Civil Registry Office of Binjai City. Starting from registration until the issuance of a registered certificate after that can provide activity reports to the Department of Population and Civil Registration binjai city through the website without having to come to the Office of Population and Civil Registration. The results of this thesis are in the form of a Binjai City Marriage Registration Information System. With such a solution the time in service will only take faster so that it becomes maximal.